The appropriate frequency and function of decidual Tim-3(+)CTLA-4(+)CD8(+) T cells are important in maintaining normal pregnancy - Wang, Songcun (Cell Death Dis, 2019)
Maternal decidual CD8(+) T (dCD8(+) T) cells must integrate the antithetical demands of maternal–fetal tolerance and anti-viral immunity to establish a successful pregnancy. T-cell immunoglobulin mucin-3 (Tim-3) and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) are two important co-inhibitory molecules that regulating CD8(+) T cells responses during infection and tumor. In the present study, we examined the co-expression of Tim-3 and CTLA-4 on CD8(+) T cells during pregnancy and found the higher frequency of Tim-3(+)CTLA-4(+)dCD8(+) T cells in response to trophoblasts. This Tim-3(+)CTLA-4(+)dCD8(+) T cells subset showed an active status and produced more anti-inflammatory cytokines. Furthermore, the decreased number and altered function of Tim-3(+)CTLA-4(+)dCD8(+) T cells correlated to miscarriage. Combined blocking Tim-3 and CTLA-4 pathways were highly effective in inhibiting the production of anti-inflammatory cytokines and were detrimental to the maintenance of pregnancy. Together, these findings supported that Tim-3 and CTLA-4 pathways might play positive roles in the establishment and/or maintenance of maternal–fetal tolerance so to promote the maintenance of normal pregnancy. So the reproductive safety must be considered, especially when anti-Tim-3/CTLA-4 antibody (and other immune checkpoint inhibitors) are used in pregnancy.